AVALIAÇÃO DA MATURIDADE DE UM SISTEMA DE GESTÃO: PROPOSTA DE UM INSTRUMENTO - Araújo, Giovanni Moraes de (2005)
The objective of this work is to evidence the importance of the security culture, environment and occupational health as critical factor of success for the implementation and continuous improvement of the integrated system of management and to consider a quantitative methodology of way evaluation. These quantitative data could be used to evaluate effectiveness of the qualification programs, training and awareness in all the levels of the organization as well as the consistency of the program and corporative lines of direction.